The Role of Parents in Shaping Children's Religious Character (Case Study in Pakandangan Sangrah Village) - Sri Nurul Annisa’; Moh. Nasir (STIT Attaqwa, 2026)
Children are assets that determine the survival, quality, and success of a nation in the future. Therefore, children need to be conditioned to grow and develop optimally and educated as well as possible so that in the future they can become the next generation with character and good personality. This study aims to determine the role of parents in shaping children's religious character and to identify supporting and inhibiting factors in Pakandangan Sangrah Village. This study uses a descriptive qualitative method with a case study type. The data collection techniques used are observation, interviews, and documentation. The subjects of this study were four families consisting of fathers and mothers. Checking the validity of the data in this study used technical triangulation and source triangulation. The results of this study indicate that the role of parents in shaping the religious character of children in Pakandangan Religious Village is by teaching about religion from an early age, carrying out good habits or uswatun hasanah, telling stories of prophets and pious people, and learning through practice. The supporting factors are motivation from parents, a supportive family, and a harmonious family. Meanwhile, inhibiting factors include children who are disobedient to their parents, a tendency to become tired from activities, resulting in difficulty listening to advice, stubbornness, aggressive behavior, and the influence of their peer group.